(untitled) (Medical Forum Monthly, 2024)
Objective: Impact of Educational Intervention for Improving Pharmacy Students’ Knowledge of Pharmacovigilance and Adverse Drug Reactions Reporting Study Design: Descriptive / cross-sectional study Place and Duration of Study: This study was conducted at the Department of Pharmacy, Lahore College of Pharmaceutical Sciences. Lahore in March 2018. Materials and Methods: In this study, 133pharmacy students of both genders from fourth and final year classes having studied clinical pharmacy were included.. Institutional ethical committee approval was taken and the students were required to sign the informed consent. Survey using a pre-validated multiple choice questionnaire to assess the knowledge of pharmacovigilance and ADR reporting amongst the students was used before and after an educational intervention containing a power point lecture on the subject. Results: 123 students returned the survey forms before and after the intervention. Student’s age was ranging from 18 to 25 years. There were 50 male students and 73 female students, 42 had rural and 81 had urban back ground. The majority of the parents had a graduate degree. Overall score pre lecture showed a Mean of 7.55 ± 1.812and the score post lecture showed a Mean of 11.74 ± 2.353 with a P-value of 0.0001. Conclusion: It is concluded that, the knowledge of pharmacovigilance and ADR reporting and awareness improved after the educational intervention. If regularly done on different forums and by different strategies this would improve the clinical practice of pharmacists by improving the ADR reporting process and culture.